The effect of surface type, collection and extraction methods on touch DNA. Issue 1 (December 2019) - Alketbi, Salem K.; Goodwin, W.
Abstract: There are different variables that affect the success of Touch DNA recovery, including surface type, the collection method used and extraction techniques. This experiment investigated how a range of porous and non-porous surfaces, different DNA collection (cotton swab, nylon flocked swab and SceneSafe Fast™ minitape) and extraction methods (PrepFiler Express BTA™ and QIAamp® DNA Investigator) affected touch DNA recovery.